Some Immunological Profile of Rheumatoid Arthritis - Abbas, Nahida R.; Mousawy, Khalida M.; Salman, Sami; Al-Kafaji, Jassim (Journal of the Faculty of Medicine Baghdad, 2006)
Seventy- four cases of clinically diagnosed Rheumatoid Arthritis (RA), fifty cases of systemic lupus erythematosus (SLE), and thirty healthy normal controls were investigated for detection of rheumatoid factor (RF), total serum immunoglobulins (Igs), antinuclear antibody (ANA), and ANA subtype anti-double stranded DNA (anti-ds DNA). Patients with RA showed 58.1% positive for RF comparable with 14% positivity in SLE patients and 6.6% in normal individuals. Serum Igs (IgA,IgG) were found to be elevated in RA and SLE patients (62.2% , 36.5%) (54% , 38%) respectively. This study revealed that ANA is found in 88% of SLE patients sera and 78% of these ANA is ds DNA in comparison with only 6.8% of RA sera were found positive for ANA.